Prevalence of Skeletal and Dental Anchorage Usage During Orthodontic Space Closure - MURUGESAN, ARATHI; S.P, SARAVANA DINESH; BALAKRISHNAN, NIVETHIGAA (The journal of contemporary issues in business and government, 2021)
Anchorage control plays a vital role in the effective management of orthodontic treatment for obtaining both structural and facial esthetics. Anchorage can be augmented by various methods. Anchorage support can be derived from the teeth or bone and is called dental anchorage or skeletal anchorage respectively. The aim of the present study was to assess the prevalence of use of skeletal anchorage and dental anchorage during space closure in all extraction cases and also to study the association between the type of anchorage used and the nature of treatment results required for the patient. This was a retrospective cross-sectional study conducted in the Department of Orthodontics, Saveetha Dental College and Hospitals, Chennai. 320 records of patients who underwent orthodontic treatment with extraction were extracted and divided into two groups based on the type of intraoral anchorage used - dental anchorage and skeletal anchorage. The samples were also divided based on the type of treatment results required for the patients, that is, pure dentoalveolar change and dentoalveolar change along with skeletal change. 28.75% patients were treated using skeletal anchorage and 71.25% patients were treated using dental anchorage. 72.19% of the selected sample required pure dentoalveolar changes whereas 27.81% of the sample required both skeletal and dentoalveolar changes. P- value of less than 0.001 was obtained as result of chi-square test indicating that there was a significant association between the type of anticipated results and the type of anchorage used. The use of conventional dental anchorage for space closure is more prevalent than skeletal anchorage. Skeletal anchorage was commonly used for patients who required both skeletal and dentoalveolar changes.